Microscopic messengers: microbiota-derived bacterial extracellular vesicles in inflammatory bowel disease - Zubair, Muhammad; Abouelnazar, Fatma A.; Dawood, Ali Sobhy; Pan, Jingyun; Zheng, Xuwen; Chen, Tao; Liu, Pengjun; Mao, Fei; Yan, Yongmin; Chu, Ying (Frontiers in Microbiology, 2024)
Inflammatory bowel disease (IBD) is a persistent and complex condition accomplished by inflammation of the gastrointestinal system, encompassing Crohn’s disease (CD) and ulcerative colitis (UC). This condition is caused by the combination of genetic predispositions, environmental triggers, and dysregulated immunological responses, which complicates diagnosis and treatment. The latest developments in gastroenterology have revealed the critical significance of the gut microbiota in the pathogenesis of IBD. Extracellular vesicles (EVs) are a type of microbial component that potentially regulate intestinal inflammation. The impact of microbiota-derived bacterial EVs (bEVs) on intestinal inflammation is mediated through several methods. They can intensify inflammation or stimulate defensive responses by delivering immunomodulatory cargo. Improved comprehension could enhance inventive diagnostic and treatment strategies for IBD. This study aimed to explore the relationship between microbiota-derived bEVs and the complex nature of IBD. We performed a thorough analysis of the formation, composition, mechanisms of action, diagnostic possibilities, therapeutic implications, and future prospects of these microbiota-derived bEVs.